In vitro digestibility of the peanut hull poultry litter in different stocking times - Oliveira, Mauro Dal Secco de; Vieira, Paulo de Figueiredo; Sampaio, Alexandre Amstalden Moraes; Nascimento, Irinéia Rosa do; Banzatto, David Ariovaldo (Pesquisa Agropecuaria Brasileira, 1991)
In order to determine the digestibility in vitro of the dry matter and of the gross energy of a peanut hull poultry litter, an experiment was carried out with a completely randomized design with four treatments and four replications. The treatments T1, T2, T3 and T4 consisted of poultry litter stocked for 0, 14, 28 and 42 days. By the in vitro digestibility technique, mean values of 48.82, 28.65, 43.54 and 37.21% were found for the dry matter, and 57.06, 45.73, 51.48 and 48.63% for the gross energy related to T1, T2, T3 and T4 treatments. The digestibility regression equations for the dry matter and gross energy were, respectively: Y = 48.82 - 4.0317x + 0.2329x2 - 0.0034x3 and Y = 57.0676 - 2.0314x + 0.1091x2 - 0.0016x3 where Y = in vitro digestibility coefficients and x = stocking times.